The Dynamics of Cultural Writing in Postmodernity - Cârstea, Daniela (Journal of Advanced Research in Social Sciences, 2021)
The article investigates the upheaval generated by the change of epistemes, from modernity to postmodernity (structuralism to poststructuralism) at the level where it is not only self-assumed, but also stated: at the writing level. On final analysis, the outlines of what might be called the “agenda” of poststructuralism will reveal an opposition to meaning, to rigid structure, to universality, to transcendence and an embracing of endless difference, of free play, of irreducible immanence, or ‘here and now’ within-the-world-ness. It conceptualises the relation to the other in general. The cultural writing thus becomes a companionship, hospitable to the movement of otherness.